2018
DOI: 10.1021/acsomega.8b01621
|View full text |Cite
|
Sign up to set email alerts
|

Berenil Binds Tightly to Parallel and Mixed Parallel/Antiparallel G-Quadruplex Motifs with Varied Thermodynamic Signatures

Abstract: Diminazene, DMZ, (or berenil) has been reported as a tight binder of G-quadruplexes. G-Quadruplex structures are often located in the promotor regions of oncogenes and may play a regulatory role in gene expression based on the stability of the folding topology. In this study, attempts have been made to characterize the specificity of DMZ binding toward multiple G-quadruplex topologies or foldamers. Mutant sequences of the G-quadruplex forming promotor regions of several oncogenes were designed to exhibit restr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…56 Interestingly, the literature has also suggested a possible mechanism of DIZE on G-quadruplex, 61 which is a target in cancer therapy. 62 Previous studies have shown evidence to support stabilisation of the mutated G-quadruplex decreased activity of c-MYC oncogene and thus allows for anti-tumour abilities [63][64][65] and that DIZE is able to bind to G-quadruplexes located in the promoter region of c-MYC oncogene. 65 F I G U R E 4 The activation of ACE2 by DIZE allows ACE2 to produce the vasoprotective peptides of the nonclassical RAS to elicit vasodilation that is important to restore in endothelial dysfunction.…”
Section: Role Of R a S In C An Cer Cell Smentioning
confidence: 99%
See 2 more Smart Citations
“…56 Interestingly, the literature has also suggested a possible mechanism of DIZE on G-quadruplex, 61 which is a target in cancer therapy. 62 Previous studies have shown evidence to support stabilisation of the mutated G-quadruplex decreased activity of c-MYC oncogene and thus allows for anti-tumour abilities [63][64][65] and that DIZE is able to bind to G-quadruplexes located in the promoter region of c-MYC oncogene. 65 F I G U R E 4 The activation of ACE2 by DIZE allows ACE2 to produce the vasoprotective peptides of the nonclassical RAS to elicit vasodilation that is important to restore in endothelial dysfunction.…”
Section: Role Of R a S In C An Cer Cell Smentioning
confidence: 99%
“…Interestingly, the literature has also suggested a possible mechanism of DIZE on G‐quadruplex, which is a target in cancer therapy . Previous studies have shown evidence to support stabilisation of the mutated G‐quadruplex decreased activity of c‐MYC oncogene and thus allows for anti‐tumour abilities and that DIZE is able to bind to G‐quadruplexes located in the promoter region of c‐MYC oncogene …”
Section: Role Of Ras In Cancer Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…The basic building blocks of G4 are the G‐tetrads which are formed by Hoogsteen G−G base pairing in the presence of cations such as Na + , K + , Pb 2+ , Li + etc [2a,b] . The G4 structures are found all through the human genome, particularly in the telomeric region, promoter oncogenes, immunoglobulin switch regions, ribosomal DNA etc [3] . Formation of G4 plays an important regulatory role in maintaining telomere and expression of oncogenes [4] .…”
Section: Introductionmentioning
confidence: 99%
“…While our proof-of-concept work was done with known duplex DNA binders, the method could be easily employed to test induced stability changes for a variety of other ligands. We note that these selected ligands have also shown binding to other nucleotide structures such as c-di-GMP and G-quadruplexes [40,41,42]. The magnitude of changes in T m upon binding of these ligands was readily observable.…”
Section: Introductionmentioning
confidence: 99%